Characterization of a Strain of Fukuyoa paulensis (Dinophyceae) from the Western Mediterranean Sea. (21st January 2016) - Laza‐Martínez, Aitor; David, Helena; Riobó, Pilar; Miguel, Irati; Orive, Emma
Abstract: A single cell of the dinoflagellate genus Fukuyoa was isolated from the island of Formentera (Balearic Islands, west Mediterranean Sea), cultured, and characterized by morphological and molecular methods and toxin analyses. This is the first report of the Gambierdiscus lineage (genera Fukuyoa and Gambierdiscus ) from the western Mediterranean Sea, which is cooler than its eastern basin. Molecular analyses revealed that the Mediterranean strain belongs to F. paulensis and that it bears LSU rDNA sequences identical to New Zealand, Australian, and Brazilian strains. It also shared an identical sequence of the more variable ITS‐rDNA with the Brazilian strain. Toxin analyses showed the presence of maitotoxin, 54‐deoxyCTX1B, and gambieric acid A. This is the first observation of the two latter compounds in a Fukuyoa strain. Therefore, both Gambierdiscus and Fukuyoa should be considered when as contributing to ciguatera fish poisoning. Different strains of Fukuyoa form a complex of morphologically cryptic lineages where F. paulensis stands as the most distantly related nominal species. The comparison of the ITS2 secondary structures revealed the absence of CBCs among strains. The study of the morphological and molecular traits depicted an unresolved taxonomic scenario impacted by the low strains sampling.